The elasticity of trade: Estimates and evidence - Ina Simonovska; Michael Waugh (University of California, Department of Economics, 2011)
Quantitative results from a large class of structural gravity models of international trade depend critically on the elasticity of trade with respect to trade frictions. We develop a new simulated method of moments estimator to estimate this elasticity from disaggregate price and trade-flow data and we use it within Eaton and Kortum's (2002) Ricardian model. We apply our estimator to new disaggregate price and trade-flow data for 123 countries in the year 2004. Our method yields a trade elasticity of roughly four, nearly fifty percent lower than Eaton and Kortum's (2002) approach. Moreover, robustness exercises result in trade elasticity estimates that are both lower and fall within a narrower range relative to the existing literature. This difference doubles the welfare gains from international trade.
Keywords: F10; F11; F14; F17; 330; elasticity of trade; bilateral; gravity; price dispersion; indirect inference